2012
DOI: 10.1016/j.rinphs.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation improves α-chymotrypsin stability upon encapsulation in poly(lactic-co-glycolic)acid microspheres

Abstract: Enhancing protein stability upon encapsulation and release from polymers is a key issue in sustained release applications. In addition, optimum drug dispersion in the polymer particles is critical for achieving release profiles with low unwanted initial “burst” release. Herein, we address both issues by formulating the model enzyme α-chymotrypsin (α-CT) as nanoparticles to improve drug dispersion and by covalently modifying it with glycans to afford improved stability during encapsulation in poly(lactic-co-gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Synthetic biodegradable polymers include poly(lactic acid) (PLA), 134 poly(glycolic acid) (PGA), 135 poly(lactic-co-glycolic acid) (PLGA), 136 poly(vinyl alcohol) (PVA), 137 PCL, 138 and polyoxyethylene (POE). They greatly differ from each other in terms of structure and properties.…”
Section: Main Types Of Bone Biomaterialsmentioning
confidence: 99%
“…Synthetic biodegradable polymers include poly(lactic acid) (PLA), 134 poly(glycolic acid) (PGA), 135 poly(lactic-co-glycolic acid) (PLGA), 136 poly(vinyl alcohol) (PVA), 137 PCL, 138 and polyoxyethylene (POE). They greatly differ from each other in terms of structure and properties.…”
Section: Main Types Of Bone Biomaterialsmentioning
confidence: 99%
“…Additionally, the directional organization of molecules on the nanoparticle periphery can help by increasing the electrophile affinity to target molecules due to the high surface area to volume ratio of NPs (62,63). Therefore, the optimum drug dispersion and homogeneity in a nanoparticle system and the linkage to cargo molecules should be well controlled and reproducible to obtain the desired therapeutic effect (64).…”
Section: Physical Properties Of Glycosylated Nanoparticlesmentioning
confidence: 99%
“…Regarding size, reports on organic and inorganic NPs indicate that glycosylation increases the size and molecular weight of NPs (14,64,65). Additionally, glycoconjugates exhibit a neutralization of zeta potential without significant alterations in colloidal stability (34,66).…”
Section: Physical Properties Of Glycosylated Nanoparticlesmentioning
confidence: 99%
“…There is also the potential for increased hydrogen bonding between the sugars on the surface of GOx and carboxylic acid units formed during PLGA degradation, resulting in increased retention of GOx within the PLGA cylinder. A previous study has demonstrated that synthetic glycosylation of a protein with a long sugar that was encapsulated within PLGA hindered the release of the protein, potentially due to similar mechanisms (Flores-Fernández and Griebenow, 2012). The slightly lower release of 50 Hz milled GOx was likely due to the localization of more GOx in one area, resulting in larger clusters of protein due to hydrogen bonding and further diminishment of release.…”
Section: Resultsmentioning
confidence: 99%